Efficacy of Esophageal Protector in Treating Gastroesophageal Reflux Disease with Extraesophageal Symptoms: a Multicenter, Open-Label, Observational Study - Yu. A. Kucheryavy; D. N. Andreyev; E. Yu. Eryomina; A. A. Gilmanov; O. V. Nazarova; Ye. A. Sidneva; Yu. G. Topalova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim: to assess effects of esophageal protector Alfasoxx on extraesophageal symptoms in patients with GERD.Materials and methods. A prospective open multicenter post-registration observational study was conducted. The study included 546 patients aged 6 to 85 years (the average age of patients is 42.4 ± 16.9 years) with a verified diagnosis of GERD (endoscopically and/or pH-metrically), the presence of extraesophageal symptoms of the disease (according to the results of an objective examination and consultations of specialists), to whom the attending physician prescribed a course of treatment with a medical device Alfasoxx in accordance with the instructions for medical use. The patients were recruited by 51 researchers in 26 cities of Russia. The study in chronological order consisted of a screening visit and two recorded visits (the observation period within the framework of the use of the Alfasoxx esophagoprotector). The screening visit was conducted on the day of the patient's admission. Visit 1 could be conducted on the same day as the screening visit, whereas visit 2 was conducted 4–5 weeks after visit 1 at the end of the course of treatment.Results. According to the results obtained, at the end of the study, 42.7 % (95 % CI: 38.5–46.9) had complete disappearance of extraesophageal GERD symptoms (questionnaire RSI = 0 points). When comparing the average values of the total RSI score before and after treatment, there was also a statistically significant regression from 13.8 points (95 % CI: 13.2–14.4) at visit 1 to 2.0 points (95 % CI: 1.8–2.2) at visit 2. Thus, the decrease in the total score was significant and exceeded 80 % of the initial value. When analyzing the dynamics of individual indicators of the RSI scale before and after treatment, a significant regression in the severity of all symptoms of the disease was noted. In addition, the results showed that the proportion of patients taking antacid-containing drugs at visit 1 significantly decreased from 58.2 % (95 % CI: 54.0–62.4) to 15.2 % (95 % CI: 12.1–18.3) by visit 2. The average score on the Likert scale of satisfaction with treatment was 4.8 (95 % CI: 4.8–4.9), whereas the convenience of using Alfasoxx is 4.7.Conclusion. This prospective observational multicenter study demonstrated that the addition of Alfasoxx to standard GERD therapy contributes to a significant regression of both esophageal and extraesophageal symptoms, as well as a decrease in the need for antacid medications.